The Impact of Capital Structure on Profitability of Commercial Banks in Ghana - Musah, Alhassan (Asian Journal of Economic Modelling, 2017)
The study examined the effect of capital structure (measures as short term debt ratio, long term debt ratio, and total debt ratio) on profitability (measured as Return on Assets and Return on equity) of commercial banks in Ghana. The study sampled 23 banking over a six year period from 2010 to 2015 and extracted data from the annual of these banks. Data was analysed using descriptive statistics, correlation analysis as well as panel regression analysis. The results showed that banks in Ghana are highly leveraged with debt financing constituting 84% of total capital out of which 77% is short term debt despite the increase in minimum equity capital of these banks. The regression analysis revealed that short term debt ratio and long term debt ratio are negatively related with profitability of banks in Ghana. However, total debt ratio was positively associated with profitability of Banks in Ghana. On the control variables, firm size, foreign ownership and age of the bank were positively associated with banks profitability whiles growth in customers’ deposits was negatively associated with banks’ profitability. The results show that commercial banks in Ghana reliance on short term financing (deposits) reduces banks profitability and as such banks should shift their financing focus from deposits to other sources. The results call for firms to choose the right mix of short term and long term debt that will maximize profitability of bank.